Evaluation of Energy-Saving Projects for Generation of Heat and Heat Supply by Prime Cost Forecasting Method - Trubaev, Pavel A.; Tarasyuk, Pavel N. (International Journal of Energy Economics and Policy, 2017)
After analyzing the current condition, it has been concluded that there are difficulties using the standard methods of economic analysis for evaluating the efficiency of energy-saving projects in systems of heat generation and heat supply for own requirements or in enterprises of monopolistic position. It is suggested to use the forecasting of the prime cost value of heat produced in prices of the accounting period instead of the discounting method, i.e. without bringing the cash flows to the united basis. The advantages of the method suggested consist in the possibility of differentiating the change of cost for each cost item, varying the change of items in different periods, forecasting the long-term development of enterprises and regions with the use of real volumes of funds for the future years, forecasting the possible risks by changing the coefficients employed and evaluating their influence on efficiency of the project. The suggested approach allows developing forecast scenarios for heat supply enterprise upgrade projects while also evaluating the effect of investments on the performances of the enterprise, selecting the required amount of investments, crediting parameters that ensure keeping growth of heat energy tariffs to the minimum. The method has been tested out for municipal heat supply organizations. Keywords: Energy saving; investments; prime cost; heat supply; long-term projects; forecasting JEL Classifications: L98; Q49